(a) 0.5m(v2^2 - v1^2) = GMm*[1/R - 1/d] where R is radius of earth; d is distance of moon, M is mass of earth and m mass of meteoroid and v1 is initial velocity and v2 that at impact

or v2^2 = 3500^2 + 2*(6.67*10^-11)*(6*10^24)*10^-6[1/6.37 - 1/384] = 0.1225*10^8 + 1.236*10^8 or

v2^2 = 1.36*10^8 or v2 = 1.16*10^4 m/s = 11.6 km/s

(b) 0.5m(v2^2 - v1^2) = GMm*[1/(R+6*10^6) - 1/d] where R is radius of earth; d is distance of moon, M is mass of earth and m mass of meteoroid and v1 is initial velocity and v2 that at impact

or v2^2 = 3500^2 + 2*(6.67*10^-11)*(6*10^24)*10^-6[1/12.38 - 1/384] = 0.1225*10^8 + 0.626*10^8 or

v2^2 = 0.7482*10^8 or v2 = 0.865*10^4 m/s = 8.65 km/s

Lorem ipsum dolor sit amet, consectetur adipiscing elit,
sed do eiusmod tempor incididunt ut labore et dolore magna aliqua. Ut enim ad minim veniam,
quis nostrud exercitation ullamco laboris nisi ut aliquip ex ea commodo consequat. Duis aute irure dolor
in reprehenderit in voluptate velit esse cillum dolore eu fugiat.

SHOW ANSWER